Usability Analysis of Udayana University SIMAK System Interface - Adiartika, Made Harry Dananjaya; Astuti, Luh Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 8 No 4 (2020): JELIKU Volume 8 No 4, Mei 2020DO - 10.24843/JLK.2020.v08.i04.p15, 2020)
With the increasingly high level of exchange of information at this time, the demand for a system capable of managing all of that information is getting higher, where one of these systems is the Udayana University Student Management Information System (SIMAK) which has a vital role in the academic administration of Udayana University, which of course requires an interface that is easy to use so that it can speed up the process of academic administration, where it is one of the things that is often taken into consideration when designing an interface that is easy to use or user-friendly, to find out whether an interface from a user-friendly system can be done by testing the usability aspects of the system. Usability is one of the important aspects that must be fulfilled for a system where to find out whether the Usability aspect of a system is fulfilled, it can be tested using the Usability Testing method with questionnaire media, this study aims to examine the Usability aspects of the SIMAK system at Udayana University using the Usability method Testing with questionnaire media, where the results of this study indicate that the SIMAK system as a whole has met the Usability component with an average value of 3, which means that the SIMAK system of Udayana University already has a good Usability aspect value.